2022
DOI: 10.3390/agronomy12051063
|View full text |Cite
|
Sign up to set email alerts
|

Karst Soil Patch Heterogeneity with Gravels Promotes Plant Root Development and Nutrient Utilization Associated with Arbuscular Mycorrhizal Fungi

Abstract: Arbuscular mycorrhizal (AM) fungi associated with plant roots play an essential role in the belowground ecological process in karst habitats with high spatial and substrate heterogeneity. However, the effects of AM fungi on root morphology and nutrient uptake under different soil patch sizes and gravel content in karst habitats are still unclear. A controlled experiment was conducted using a square device divided into 16 grid patches. This experiment had three treatments, including the mycorrhizal fungal treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“…Bidens pilosa L. is an annual herb of the Asteraceae and is widely distributed in the karst areas of southwest China ( Li et al., 2021 ). B. pilosa is the typical pioneer succession species of karst vegetation documented by our field surveys, and our previous found that it has a high rate of mycorrhizal colonization ( He et al., 2019 ; Han et al., 2020 ; Li et al., 2022 ; Sun et al., 2022 ). Therefore, B. pilosa was selected as the plant material in this study.…”
Section: Methodssupporting
confidence: 59%
“…Bidens pilosa L. is an annual herb of the Asteraceae and is widely distributed in the karst areas of southwest China ( Li et al., 2021 ). B. pilosa is the typical pioneer succession species of karst vegetation documented by our field surveys, and our previous found that it has a high rate of mycorrhizal colonization ( He et al., 2019 ; Han et al., 2020 ; Li et al., 2022 ; Sun et al., 2022 ). Therefore, B. pilosa was selected as the plant material in this study.…”
Section: Methodssupporting
confidence: 59%
“…Several investigations into the mechanism of action of nutrient absorption and translocation with AMF have found that: i. The mycorrhizal hyphae can stretch and explore a larger region of the ground soil than the roots of the host plant can achieve, thereby enabling it to gain access to both micro and macronutrients that the plant alone is unable to absorb [17]. Hence, AMF can cross the depletion zone caused by the plant's quick uptake of nutrients in the region around its root system and provide the appropriate nutrient elements to the plant [12].…”
Section: The Function Of Arbuscular Mycorrhizal Fungi In Soil Nutrien...mentioning
confidence: 99%
“…According to the CSR theory of Grime (1977), the S strategy plants are mainly for survival by stress-tolerance in harsh habitat conditions, and the C strategy plants are mainly for conquest through competition due to scarce resources, while the R strategy plants are mainly for reproduction through increasing individuals of a population [2]. In particular, the karst maintains a lower resource of N and P and a barren soil layer with higher heterogeneous habitat [4,57,58], leading to adverse habitat conditions and scarce habitat resources. Therefore, competing for limited N and P resources through stress tolerance for individual survival is necessary as the optimal strategy of S with C in adverse karst habitats to maintain fewer family members.…”
Section: The Ecological Strategy In the Karst Forestsmentioning
confidence: 99%
“…Specifically, strategy C is mainly to improve the competitive ability, strategy S is mainly to grow maintenance under limited resource conditions, and strategy R is mainly to cycle fast for life reproduction in suffering frequent interference [2,3]. CSR theory can not only be adopted to explain the ecological process of community integration, biodiversity maintenance, and vegetation succession [4][5][6], but also the ecosystem function productivity and community stability [7,8]. Plant survival Forests 2023, 14, 1258 2 of 14 could be reflected by ecological strategies via plant functional traits responding to environmental changes [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation